RRM2B mutations are frequent in familial PEO with multiple mtDNA deletions - Carl Fratter; Pravrutha Raman; Charlotte L. Alston; Emma L. Blakely; Kelly Jean Thomas Craig; Conrad Smith; Julie Evans; A Seller; Birgit Czermin; Michael G. Hanna; Joanna Poulton; Charlotte Brierley; et al. (2011)
Disorders of mitochondrial DNA (mtDNA) maintenance leading to multiple mtDNA deletions are a significant cause of inherited neurologic disease in adults, but the underlying nuclear gene defects remain elusive in many patients.Following the recent description of a truncating mutation in the RRM2B gene-encoding the small subunit, p53R2, of the p53-inducible ribonucleotide reductase protein-in 2 families with autosomal-dominant progressive external ophthalmoplegia (adPEO), 1 we determined the frequency of RRM2B mutations in a large cohort of patients with PEO and multiple mtDNA deletions in muscle in whom mutations in all known candidate genes (e.g., POLG, POLG2, SLC25A4, and PEO1) had been excluded. 2Methods.We studied 75 unrelated probands with PEO, a mosaic defect of cytochrome c oxidase (COX) activity, and multiple mtDNA deletions in skeletal muscle who had been referred to Mitochondrial Diagnostic Centers at Newcastle, Oxford, or Munich for clinical assessment and histologic/molecular genetic analysis.The entire coding region, including intron-exon boundaries, of the RRM2B gene was determined as previously described. 1RRM2B exon copy number (exons 1-8) was assessed by MLPA (MRC-Holland kit P089-A1) in patients with single, heterozygous missense mutations. Standard protocol approvals, registrations, and patient